RANCANGAN SISTEM INFORMASI SISWA PADA SEKOLAH DASAR NEGERI 46/IV KOTA JAMBI - Sri Mulyati; Lina Restita Sari (JURNAL AKADEMIKA)
State Elementary School 46 / IV City of Jambi now has a computer , but has not been fully utilized by each homeroom teacher and the administration so that the student data processing system is not perceived as optimal as possible. Student data processing system is not considered to be effective , especially in terms of speed , accuracy and neatness of the information produced. With the application of information systems students at the State Elementary School 46 / IV City ofJambi this problem can be overcome , so that the information presented can be faster.